Study the Effect of Hyperthyroidism on Heart Function by Using BNP as Indicator - Fallah Allawi, Ahmed; A. Al-Mahdawi, Ferial; Y. Al-Samerraie, Abdul-Karim (Iraqi Journal of Science, 2026)
The aim was made to specify the effect of hyperthyroidism on B-type natriureticpeptide (BNP) level. Twenty patients with hyperthyroidism, 20 patients withhyperthyroidism treated with (35) mg Carbimazole, 12 patients withhyperthyroidism associated with heart failure and 20 healthy participants wereincluded in this study. Serum Triiodothyronine (T3), Thyroxin (T4) and Thyroidstimulating hormone (TSH) have been used for hyperthyroidism diagnosis test, alsoserum BNP level was measured. The results showed that the mean ± SE of serumBNP was significantly (P<0.05) increased in hyperthyroid group (420.76 ± 83.43)pg/mL and hyperthyroid with heart failure group (728.58±149.06) pg/mL whencompared with the control group (23.18 ±10.10) pg/mL. While, no significant(P>0.05) differences between hyperthyroid treated with (35) mg carbimazole group(65.00 ± 16.21) pg/mL and control group (23.18 ±10.10) pg/mL. But, there was asignificant (p<0.05) decrease in serum BNP level in hyperthyroid treated with (35)mg carbimazole group when compared with the hyperthyroid group andhyperthyroid with heart failure group. The present study demonstrated that thehyperthyroidism may lead to impaired heart function, and thus the high level of theBNP hormone